Microbial drivers of methane and sulfur cycles in Amazonian floodplain and upland soils: diversity, interactions, and climate change responses - Gontijo, Júlia Brandão (2023)
Floodplains in the lowland Amazon Basin are ecosystems that experience periodic flooding events due to large seasonal variations in rainfall. They play a critical role in regional biogeochemical cycles and significantly contribute to the global carbon budget. It is estimated that floodplains are the largest natural source of methane (CH4) emission to the atmosphere in the tropics. This contrasts to upland forests, known for their CH4 sink capacity. The net CH4 fluxes in these soils is, however, dependent on the activity of CH4-oxidizing organisms and their interactions with other biotic and abiotic factors. In this sense, the S-cycle may have na important role on the CH4 fluxes balance in the region, however, little is known about the microbial interactions between CH4 and S cycles in Amazonian floodplains and upland forest. Despite their major importance, the microbial communities associated with these processes and their responses to natural and anthropogenic changes are still poorly understood. Understanding how microbial key players of the biogeochemical cycles in Amazonian floodplains and upland forests function is necessary to predict future scenarios, particularly given the reported impacts of climate change and the microbial feedbacks on the functioning of the Amazon basin. In this thesis, we aimed to investigate: i) the microbial interactions between CH4 and S cycles in the field based on metagenomic sequencing and co-occurrence networks; ii) the microbial feedbacks to climate change effects (temperature rising and flooding) through a microcosm experiment followed by 16S rRNA amplicon sequencing and qPCR; and iii) the genomic potential of a metagenome-assembled genome of a methanotroph from Amazonian floodplains. The results from the field study suggest the potential role of the S cycle in stimulating and mitigating CH4 emissions in Amazonian floodplains and uplands soils, depending on the co-occurrence of different microbial S and CH4-related metabolisms. Regarding the microcosm experiment, our data indicate the CH4 cycle dynamics and microbial communities from the Amazonian floodplain and upland forest soils respond differently to climate change effects, and upland forest microbial communities are sensible to the temperature rising. We also reported the potential role of anaerobic CH4 oxidation against global warming in Amazonian floodplains. By exploring the genomic potential of a Methylocystis MAG, we found that different genomic strategies, including genes related to N metabolic pathways as well as motility capacity, may contribute to the niche occupancy of this aerobic methanotroph in Amazonian floodplains. Based on our discussions, we expanded the knowledge on the potential microbial CH4-cycling drivers in Amazonian floodplain and upland forests, as well as their interactions with the S-cycle, and the potential and important role of aerobic and anaerobic CH4 oxidation pathways in controlling CH4 emissions in our studied sites.